2009
DOI: 10.1111/j.1468-2958.2008.01341.x
|View full text |Cite
|
Sign up to set email alerts
|

Family Communication Patterns and Relational Maintenance Behavior: Direct and Mediated Associations with Friendship Closeness

Abstract: In this study, both face-to-face and online relational maintenance behaviors were tested as mediators of family communication patterns and closeness with a same-sex friend. Participants included 417 young adults recruited from communication courses at a large university in the Midwestern United States. The obtained structural model demonstrated that family communication patterns are associated with friendship closeness though face-to-face and online maintenance behaviors fully mediate this association. Specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
56
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(61 citation statements)
references
References 35 publications
3
56
0
2
Order By: Relevance
“…When asked about their computer usage experience, participants indicated a mean of 8.99 years (SD 02.91) of computer use, 6.42 years (SD 02.10) of e-mail use, and 5.55 years (SD02.92) of instant messenger use. Data from this population were used in a concurrent study of relational maintenance behavior (Ledbetter, 2009). …”
Section: Methods Participantsmentioning
confidence: 99%
“…When asked about their computer usage experience, participants indicated a mean of 8.99 years (SD 02.91) of computer use, 6.42 years (SD 02.10) of e-mail use, and 5.55 years (SD02.92) of instant messenger use. Data from this population were used in a concurrent study of relational maintenance behavior (Ledbetter, 2009). …”
Section: Methods Participantsmentioning
confidence: 99%
“…When family communication is understood from the perspective of family schemata, relationships can be uncovered explaining behaviors both within and beyond the family (Fitzpatrick & Ritchie, 1994;Ledbetter, 2009;Schrodt, 2009;Scrodt & Ledbetter, 2007). Family members' behaviors are shaped by how they understand communication within particular relationships, within particular types of relationships, and in general social situations.…”
Section: Discussionmentioning
confidence: 99%
“…However, Ledbetter (2009) examined the mediating role of maintenance behaviors on the relationship between family communication patterns and friendship closeness. He concluded that maintenance Western Journal of Communication 49 behaviors fully mediated the relationship between both conformity and conversation orientations with friendship closeness.…”
Section: Relational Maintenancementioning
confidence: 99%